PENGARUH KOPERASI YANG DIKELOLA MASJID DALAM PEMBERDAYAAN EKONONOMI MASYARAKAT (Studi Pada Koperasi Masjid Sabilillah Kota Malang) - Primananda Rafif (Jurnal Ilmiah Mahasiswa FEB, 2016)
The essens of economic problems operating almost all business sectors is in the field of capital. Microfinance institutions especially cooperatives and using the concepts of Islamic economics is one of the institutions or financial institutions that can help micro business actors in meeting the problems in the field of capital, especially the business on the national scale down. The purpose of this study is to analyz the cooperative managed by the mosque in the economic empowerment of society to the prosperity of micro business. The approach used  in this study is a quantitative approach with respondents. The method used in this research is Ordinary Least Square (OLS) method. Based on the result of multiple linear regression analysis using SPSS 06 statistical program, show capital aid and business duration positively affect the income of cooperative customers sabilillah. With the availability of two elements of cooperative microfinance institutions and mosques can synergize by providing solutions and the following problems special economic field for Muslims, in which religious institutions and economics can be harmonized can be seen from development of economic empowerment of mosque-based sosiety.Keywords: Mosque Based Empowerment, Micro Business Actors, Multiple Linear Regression, OLS, Welfare